A comparative study on knowledge and perception of vector borne diseases among rural and urban population in Tamil Nadu - V., Roselin; V., Srisanthanakrishnan (International Journal Of Community Medicine And Public Health, 2019)
Background: Vector-borne diseases (VBD) remain a major public health challenge, in India. Knowledge about VBD, social, demographic and environmental factors strongly influence the vector transmission and results in major outbreaks. Hence this study was conducted to assess knowledge and practice along with environmental conditions prevailing in both rural and urban areas. Methods: Cross sectional study was conducted in rural and urban field practice area of Sri Muthukumaran Medical College and Research Institute, Chennai, during June 2018 to December 2018. A total of 472 participants with 236 participants from each urban and rural area were included. Data was collected using proforma and analysis was done using SPSS 16. Results: Knowledge about VBD like dengue was 63.6% and 76.7% among rural and urban population, respectively. Similarly malaria was known by knows 59.3% and 68.2% of rural and urban participants. Japanese Encephalitis was the least known mosquito borne disease in both the groups. (p=0.0136). Common breeding sites addressed by the rural population were artificial collected water (36.9%) and urban population was dirty water (42.8%). Conclusions: Knowledge and practice of preventing vector borne disease is still lacking among both rural and urban participants. Spreading knowledge about VBD is a part in effective vector borne disease control which can be achieved by community education alone rather than insecticides and sprays.